Gross Biometrical Studies on Male Accessory Genital Glands of Bakerwali (Kaghani) Goat - Nissar, Shazia; Suri, Shalini (Indian Journal of Veterinary Anatomy, 2012)
The study was conducted on male accessory genital glands of thirty five Bakerwali(Kaghani) goats. Glands were fixed in 10% neutral buffered formalin and 90% chilled alcohol. Biometrical measurements like length, width, thickness, weight and volume of ampulla of vas deferens, seminal vesicle, prostate and bulbourethral gland were recorded and analyzed statistically.